CITRA ISTRI DALAM KUMPULAN NOVELET DUNIA TANPA WARNA KARYA MIRA W (Sebuah Kajian Sastra Feminis) - Martha, Nia Ulfa (IAIN Pekalongan, 2010)
Abstract: Research on the collection of A World Without Color novelet W Mira's work aims to describe the imaging wife in a collection of A World Without Color novelet W Mira's work and social environment to describe the link with imagery wife. The method used is the sociology of literature that focuses on text analysis. The results obtained in the study include wives as wives and wives as mothers. Wife as a wife tercitra as a highly loyal, obedient, patient, understanding, responsible, caring, firm establishment, seriously, respect their husbands, rebellious, not easily discouraged, self-centered, low self-esteem, easily discouraged, and angry. Wife as a mother tercitra as a loving figure, left the children, responsible, caring, educating, caring, and grumpy. Based on social relations with the figures of the wife in a collection of A World Without Color novelet W Mira's work is known figures wife have ambivalent nature. On the one hand they accept traditional gender roles. However, on the other hand they reject traditional gender roles.